2021
DOI: 10.1186/s40100-021-00197-1
|View full text |Cite
|
Sign up to set email alerts
|

Why consumers drink natural wine? Consumer perception and information about natural wine

Abstract: Similar to other foods, the concept of natural wine is much debated due to the lack of a clear and regulated definition, leading to a proliferation of heterogeneous norms and standards proposed from different natural wine associations at national levels. The current study explored the aspects which mediate individuals’ information and perception of natural wine, and the rationale behind natural wine consumption behavior among Italian (n = 501) and Spanish (n = 527) regular wine consumers. The results reveal a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
0
27
0
1
Order By: Relevance
“…As a result of this controversy, consumers tend to confuse NW with wines without sulfites (D'amico et al, 2016;Amato et al, 2017), as well as organic, and biodynamic (Jones and Grandjean, 2018). Nonetheless, it has been shown that consumers acquainted with NW are willing to pay more for it, in various contexts (Galati et al, 2019;Migliore et al, 2020;Vecchio et al, 2021).…”
Section: Policy Antecedentsmentioning
confidence: 99%
“…As a result of this controversy, consumers tend to confuse NW with wines without sulfites (D'amico et al, 2016;Amato et al, 2017), as well as organic, and biodynamic (Jones and Grandjean, 2018). Nonetheless, it has been shown that consumers acquainted with NW are willing to pay more for it, in various contexts (Galati et al, 2019;Migliore et al, 2020;Vecchio et al, 2021).…”
Section: Policy Antecedentsmentioning
confidence: 99%
“…Istraživanje Goudis i Skuras (2020) ukazuje da grčki potrošači imaju visok nivo svesti i informisanosti o oznakama geografskog porekla koje se ogleda u mogućnosti prepoznavanja određenih simbola ili oznaka kvaliteta na tržištu. Potrošačima u Italiji sa višim nivoom znanja oznake predstavljaju glavni motiv u procesu kupovine i osnov za donošenje odluka (Vecchio & Annunziata, 2011). Prema istraživanju Wilson (2002) italijanski, grčki i francuski ispitanici više su upućeni u sistem oznaka geografskog porekla u poređenju sa ispitanicima u severnoevropskim zemljama.…”
Section: Uvodunclassified
“…Consumers in developed countries have become more informed, critical and demanding in their food choices, with an expanding tendency to demand sustainable, organic and natural wines (Alonso Gonz alez and Parga-Dans, 2020a;Grunert, 2005;Halkier et al, 2007), and a growing willingness to pay for them (Costanigro et al, 2014;Lanfranchi et al, 2020;Saliba et al, 2013). Research shows that consumers are increasingly committed to healthy eating habits and more willing to pay for wines that are healthy, sustainable, local, responsible, etc (Vecchio et al, 2021). Similarly, producers are trying to differentiate…”
Section: Introductionmentioning
confidence: 99%
“…, 2013). Research shows that consumers are increasingly committed to healthy eating habits and more willing to pay for wines that are healthy, sustainable, local, responsible, etc (Vecchio et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%